CGE Analysis of regional policy in the Northern Kyushu area. - Hiroshi Sakamoto (Penerbit Universiti Kebangsaan Malaysia, 2011)
This study develops a policy model in the context of the hierarchical administration system for a regional economy in Japan. In Japans case as a hierarchy of national, prefectural, and municipal (city) administration exists, a different regional policy is established for each level of the level of the hierarchy. Generally, the policy and its evaluation differ according to the priorty given either to national interests or to earch regions interests. This was examinated by conducting a quantitative analysis using the computable general equilibrium (GCE) model.Particularly, Kitakyushu and Fukuoka cities constitute and administrative region at the city level.Moreover, these two cities along with the rest of Fukuoka prefecture represent Fukuoka prefecture.Alternatively,a case for including the adjacent prefecture, Yamaguchi prefecture in these regions exists. The entire area is called the Northern Kyusu area by combining Fukuoka and Yamaguchi prefectures. Such a large area gains importance in regional policy because it is placed higher in the hierarchy. This study focuses on five regions, including the rest of japan.Moreover, given the availability of the input-output tables for these regions, the database to develop the GCE model can be estimed after tabulating the interregional input-output table.